Artificial Macrophage with Hierarchical Nanostructure for Biomimetic Reconstruction of Antitumor Immunity - Zhao, Henan; Liu, Renyu; Wang, Liqiang; Tang, Feiying; Chen, Wansong; Liu, You‑Nian (Nano-Micro Letters, 2023)
Artificial cells are constructed from synthetic materials to imitate the biological functions of natural cells. By virtue of nanoengineering techniques, artificial cells with designed biomimetic functions provide alternatives to natural cells, showing vast potential for biomedical applications. Especially in cancer treatment, the deficiency of immunoactive macrophages results in tumor progression and immune resistance. To overcome the limitation, a BaSO4@ZIF-8/transferrin (TRF) nanomacrophage (NMΦ) is herein constructed as an alternative to immunoactive macrophages. Alike to natural immunoactive macrophages, NMΦ is stably retained in tumors through the specific affinity of TRF to tumor cells. Zn2+ as an “artificial cytokine” is then released from the ZIF-8 layer of NMΦ under tumor microenvironment. Similar as proinflammatory cytokines, Zn2+ can trigger cell anoikis to expose tumor antigens, which are selectively captured by the BaSO4 cavities. Therefore, the hierarchical nanostructure of NMΦs allows them to mediate immunogenic death of tumor cells and subsequent antigen capture for T cell activation to fabricate long-term antitumor immunity. As a proof-of-concept, the NMΦ mimics the biological functions of macrophage, including tumor residence, cytokine release, antigen capture and immune activation, which is hopeful to provide a paradigm for the design and biomedical applications of artificial cells. Highlights: 1 An artificial macrophage with hierarchical nanostructure (BaSO4@ZIF-8/TRF NMΦ) is constructed as an alternative to immunoactive macrophages. 2 The Zn2+ chemical messenger as an “artificial cytokine” is released from the artificial macrophage to induce tumor anoikis and enhance immunogenicity. 3 The artificial macrophage can efficiently capture tumor antigens for antigen presentation and T cell activation to fabricate long-term antitumor immunity, successfully mimicking the basic functions of natural immunoactive macrophage.